Online Purchase Decision: do Price Perception, Product Knowledge, and Ease of Shopping Affect Consumption? - Sri Lestari; Ambuy Sabur; Litha Azzahra Maulidiah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The subjects in this study were student Universitas Islam Syekh-Yusuf in 2020, totaling 98 respondents, using the technique of proportionate stratified random sampling. Multiple regression was used to analyze the data both descriptively and quantitatively. Statistical tests show that the model is 44,3 percent accurate as a predictor. Price perception influences online purchase decisions in a positive and significant way. Product knowledge has no bearing, but shopping convenience impacted on online purchase decisions. Meanwhile, price perception, product knowledge, and shopping convenience all impacted on online purchase decisions. The result of this study recommends to business people in displaying product information features clearly to make it easier for consumers to make online purchases so that consumers will continue to use them. Further research should examine other factors that influence online purchasing decisions such as trust, information quality, brand image, and promotion.